The relationship between trunk control in sitting and during gait in children and adolescents with cerebral palsy. (20th November 2014) - Sæther, Rannei; Helbostad, Jorunn L; Adde, Lars; Brændvik, Siri; Lydersen, Stian; Vik, Torstein
<x xml:space="preserve">Abstract</x> Aim To assess the relationship between trunk control in sitting and trunk control during gait in children and adolescents with cerebral palsy (CP). Method Twenty‐six children (17 males, nine females) with spastic CP (Gross Motor Function Classification System I–III [15 unilateral, 11 bilateral], mean age 13.5y), were included. Trunk control in sitting was assessed with the Trunk Impairment Scale (TIS) and the Trunk Control Measurement Scale (TCMS), and trunk control during gait by a trunk‐worn accelerometer. The Pearson's rank correlation coefficient, partial correlation (rp), and linear regression analysis were applied to assess the relationship between trunk control in sitting and during gait. Results Trunk control in sitting assessed with the TCMS and the TIS total scores both correlated with trunk accelerations during gait (rp=0.67 and 0.60 respectively). Moreover, some subscale scores correlated equally well with trunk control during gait (the TCMS dynamic sitting balance‐reaching subscale score [DSB‐R]; rp=0.61) or even higher (TIS dynamic sitting balance subscale [DSB]; rp=0.66). Interpretation Trunk control in sitting has a moderate to good correlation with trunk control during gait. Our results suggest that the subscale DSB‐R of the TCMS, being less time consuming, may be applied in clinical assessment to gain information on trunk control during gait. Future studies are needed to explore how this information may be applied in the planning of 'gait interventions'.